Tiếp cận tích hợp trong giáo dục văn hóa ứng xử học đường cho sinh viên đại học sư phạm: Cơ sở lí luận và định hướng vận dụng - Nguyễn, Thuý Quỳnh; Vũ, Lệ Hoa (Tạp chí Giáo dục, 2025)
In the context of higher education facing increasing pressure to innovate in order to meet the requirements of the 2018 General Education Program and the Professional Standards for Teachers, equipping pedagogical students with school cultural behavior has become an urgent task. Therefore, examining the theoretical and practical foundations of the integrated approach in school cultural behavior education is essential to identify effective solutions. The article aims to clarify the theoretical foundations of the integrated approach and to propose orientations for its application in school cultural behavior education for pedagogical students. Based on an analysis and synthesis of both domestic and international studies on the integrated approach, the research identifies its essence, characteristics, advantages, and principles of application. The findings indicate that the integrated approach is meaningful in shaping and developing school cultural behavior, particularly when implemented through experiential learning, group activities, and projectbased learning. Accordingly, the article proposes five groups of cultural behavior education contents following the integrated orientation, along with suggestions on methods, organizational forms, and assessment criteria. These orientations not only contribute to enriching the theoretical foundation but also provide practical grounds for designing courses or modules on school cultural behavior education in teacher training institutions.